DESIGN OF PERFORMANCE MANAGEMENT SYSTEMS FOR PT NIION INDONESIA UTAMA - Maidy Tamara P., Anditha
In Indonesia, business in the creative industry sector is growing rapidly. This creative industry has huge potential for business people in Indonesia. Because the fashion industry provides the second-largest contribution in the creative economy by 18.15% (Based on data from the Creative Economy Agency).